Viability resources of urban dwellers: The experience of comparing two cities - Tatyana P. Emelyanova; Eva N. Vikentieva; Lyudmila V. Shibayeva; Nataliya I. Khokhlova (Saratov State University, 2022)
The relevance of the study is due to the identification of unique and universal viability resources of the Moscow and Surgut residents. The purpose of the research is to study the viability resources of Moscow and Surgut citizens. The study hypothesizes that there are general and unique personal and environmental factors for both cities that ensure the viability of their residents. The study was carried out on a sample of respondents aged 18-75 (N = 644) living in the two cities: Moscow (n = 359) and Surgut (n = 285). The applied methods include the "Identification-with-the-City Scale" (M. Lally) used to identify the perception of the advantages of the city, general attachment to it, connection with the city past and orientation to it in the future. Moreover, the authors used the original questionnaires aimed at the identification of the citizens' responsibility and their willingness to participate in the city life (T. V. Drobysheva); analysis of the emotional characteristics of the city future "Semantic differential" (T. V. Drobysheva, S. V. Tarasov); a set of questions that reveal socio-demographic characteristics of the respondents. The research results demonstrate that there are some factors of the urban environment that reduce the citizens' viability. These factors are common to both cities. In addition, in the Moscow sample, the experience of stress is mostly associated with external factors, while in the Surgut sample it is connected with the quality of life. The study has revealed differences in the socio-psychological resources of the citizens' vitality: in the level of urban identity, in the type of responsibility (external for the Muscovites and internal for the Surgut residents), in readiness for various types of activity, in the image of the future city, and in the use of environmental resources. The resources of the Muscovites' viability are based on a high level of their urban identity, on delegating responsibility for the city state to the authorities, and on a positive image of future life in the city. The Surgut residents rely on their self-confidence and feel responsible for the city state. An important viability resource for them is their willingness to take actions in the interest of the city and their tendency for active use of urban recreational resources. It is recommended to develop urban programs to attract interested citizens to planning city innovations in both cities.